2020
DOI: 10.3389/fcell.2020.585644
|View full text |Cite
|
Sign up to set email alerts
|

Bone and Muscle Crosstalk in Aging

Abstract: Osteoporosis and sarcopenia are two age-related diseases that affect the quality of life in the elderly. Initially, they were thought to be two independent diseases; however, recently, increasing basic and clinical data suggest that skeletal muscle and bone are both spatially and metabolically connected. The term “osteosarcopenia” is used to define a condition of synergy of low bone mineral density with muscle atrophy and hypofunction. Bone and muscle cells secrete several factors, such as cytokines, myokines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 179 publications
(308 reference statements)
3
81
0
1
Order By: Relevance
“…Additionally, grip strength was also a significant contributor to the model, further supporting the idea that the association between BMD and SB is mediated by muscle strength. This finding reinforces the idea of the crosstalk between muscle and bone, suggesting a shared pathological process in older adults [ 14 , 61 ]. Previous studies reported the negative impact of SB, independently of PA, on bone integrity [ 62 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, grip strength was also a significant contributor to the model, further supporting the idea that the association between BMD and SB is mediated by muscle strength. This finding reinforces the idea of the crosstalk between muscle and bone, suggesting a shared pathological process in older adults [ 14 , 61 ]. Previous studies reported the negative impact of SB, independently of PA, on bone integrity [ 62 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, several scientific studies agree that both tissues perform an important endocrine function, whose products, represented by osteokines for bone tissue and myokines for muscle tissue, have been proposed as possible key players in bone–muscle crosstalk [ 2 , 6 , 33 ]. Levels of these signal molecules can also vary with age and physical activity [ 34 ]. Therefore, the identification of these molecules and understanding their role within the bone–muscle system is currently a major challenge to identify potential pharmacological targets and to prevent and/or treat bone–muscle diseases related to aging and sedentariness.…”
Section: Bone–muscle Crosstalk: Mechanical and Biochemical Aspectsmentioning
confidence: 99%
“…miRNAs are a class of small non-coding RNAs that play key roles in controlling skeletal muscle development [ 6 ]. In the past decade, the ability of miRNAs to bind the 3’-UTR of target mRNAs to perform biological functions has been widely accepted [ 7 , 8 ]. For example, miR-206 played a key role in enhancing slow skeletal muscle and muscular dimorphism [ 9 ].…”
Section: Introductionmentioning
confidence: 99%